Cardiac venous malformation concurrent with multiple hepatic venous malformations: A case report - Zhang, Shijie; Xu, Zhenqiang; Zou, Chengwei; Zhang, Gang (Frontiers in Cardiovascular Medicine, 2022)
A 50-year-old woman who had previously undergone right radical mastectomy presented with chest tightness and shortness of breath after physical activities. A cardiac mass and multiple hepatic lesions were successively detected. We first performed hepatic puncture biopsy. Histopathologic examination confirmed that the multiple hepatic lesions were venous malformations. Based on the imaging findings and previous reports in the literature, we boldly speculated that the cardiac mass was also a venous malformation. The cardiac venous malformation was successfully resected, and the postoperative pathology confirmed our suspicion.